Endothelial keratoplasty with infant donor tissue - Kobayashi, Akira (Dove Medical Press, 2014)
Here we report a case of endothelial keratoplasty with infant donor tissue obtained after brain death. A 52-year-old man with endothelial dysfunction of unknown cause in the right eye underwent non-Descemet stripping automated endothelial keratoplasty (nDSAEK) with tissue from an infant donor (2 years). Intraoperative and postoperative complications were recorded. Best corrected visual acuity and donor central endothelial cell density were recorded preoperatively and postoperatively. Infant donor tissue preparation with a microkeratome set at 300 μm was successful; the donor tissue was extremely elastic and soft compared with adult tissue. The central endothelial cell density of the infant donor tissue was as high as 4,291 cells/mm(2). No complications were observed during donor tissue (8.0 mm in diameter) insertion with the double-glide technique (Busin glide with intraocular lens sheet glide) or any of the other procedures. Best corrected visual acuity improved from 1.7 logMAR (logarithm of the minimum angle of resolution; 0.02 decimal visual acuity) preoperatively to 0.2 logMAR (0.6) after 6 months and 0.1 logMAR (0.8) after 1 year. The central endothelial cell density after 6 months was 4,098 cells/mm(2) (representing a 4.5% cell loss from preoperative donor cell measurements), and the central endothelial cell density after 1 year was 4,032 cells/mm(2) (6.0% decrease). Infant donor tissue may be preferably used for DSAEK/nDASEK, since it may not be suitable for penetrating keratoplasty or Descemet membrane endothelial keratoplasty.